Envisioning the Future: Laibach as a Challenger of the Yugoslav State - Stefancic, Mitja (Scenari, 2024)
This contribution aims to assess Laibach’s disruptive social and cultural contribution by analysing the cultural pattern of the early 1980s and discussing the strategies applied by the group to overcome official bans such as the prohibition to publicly use the name “Laibach”. It analyses interviews to contemporary intellectuals who are established experts on the ensemble. The interview questions focused on Laibach’s relation to the Slovenian independent culture, the political pressure experienced by the band during its early years, and the group’s positioning in a setting which became functional for promoting Slovenia’s call for independence. The paper argues that the band’s critique was directed towards the repressive Yugoslav state and its inability to find solutions to economic and social problems rather than towards socialism as such. Laibach’s example shows that governments claiming to support freedom should pay adequate attention to radical art movements and alternative spaces by proactively supporting them.